1996
DOI: 10.1006/dbio.1996.0102
|View full text |Cite
|
Sign up to set email alerts
|

The PH-20 Protein in Cynomolgus Macaque Spermatozoa: Identification of Two Different Forms Exhibiting Hyaluronidase Activity

Abstract: In these experiments, we have characterized the bifunctional sperm protein PH-20 in macaque sperm and studied its hyaluronidase activity. Intact sperm were evaluated before the acrosome reaction (AR), and a soluble form of PH-20 released during acrosomal exocytosis was also investigated. Western blots of SDS-PAGE of acrosome-intact sperm extracts revealed a 64-kDa form of PH-20 was recognized by a polyclonal antibody (R-10) raised in rabbits against purified, recombinant cynomolgus macaque sperm PH-20. The sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 0 publications
9
83
0
Order By: Relevance
“…These data may weaken the possibility that the ZP-binding domains of Hyal5 and PH-20 function in the sperm-egg interaction. It has been reported that two forms of hyaluronidase are present in sperm of several mammalian species: PH-20 GPI-anchored on the plasma and inner acrosomal membranes and a soluble enzyme (sPH-20) released during acrosome reaction (17,34,35). In cynomolgus macaque, the GPI-anchored form exhibits the maximum activity at neutral pH, whereas sPH-20 is active only at acid pH (34,35).…”
Section: Resultsmentioning
confidence: 99%
“…These data may weaken the possibility that the ZP-binding domains of Hyal5 and PH-20 function in the sperm-egg interaction. It has been reported that two forms of hyaluronidase are present in sperm of several mammalian species: PH-20 GPI-anchored on the plasma and inner acrosomal membranes and a soluble enzyme (sPH-20) released during acrosome reaction (17,34,35). In cynomolgus macaque, the GPI-anchored form exhibits the maximum activity at neutral pH, whereas sPH-20 is active only at acid pH (34,35).…”
Section: Resultsmentioning
confidence: 99%
“…Following the acrosome reaction PH-20 is present on the inner acrosomal membrane and on the plasma membrane overlying the equatorial segment, indicating that PH-20 may migrate from the plasma membrane of the posterior sperm head to the inner acrosomal membrane after acrosomal exocytosis. A soluble form of monkey PH-20 is also released during the acrosome reaction (Cherr et al, 1996). It is thus conceivable that the localization of mouse Ph-20 and Hyal5 is essentially similar to that of guinea pig and monkey PH-20 on the acrosome-intact and acrosome-reacted sperm, although we need to ascertain the PH-20 migration during the acrosome reaction.…”
Section: Sperm Penetration Through the Cumulus Massmentioning
confidence: 99%
“…The 2 bands may represent the 2 forms of the enzyme, related to the soluble and membrane-bound forms of PH-20. 16,17 Separation of the 2 forms of the enzyme, the 75 and 58 kDa bands, was achieved by tandem gel filtration on Superose 12. Single bands were obtained on SPAGE, indicating that there was not equilibrium between the 2 forms of the enzyme (Fig.…”
Section: Preparation Of Hyaluronidasementioning
confidence: 99%